Answer:
Step-by-step explanation:
1) 2x -y = 1 -------1
3x - y = -6 ------2
Subtract eqn 2 from eqn 1
-x = 1--6 = 7
x = -7
Put x= -7 in eqn 1
2*-7-y = 1
-14-y = 1
- y = 15
y = -15
2) 4x +2y = 10------1
y = 4x + 2--------2
Put eqn 2 in eqn 1
4x + 2 ( 4x+ 2) = 10
4x + 8x + 4 = 10
12x = 6
x = 6/12 = 1/2
Put x = 1/2 in eqn 2
y = 4* 1/2 + 2= 2 + 2
= 4
3) 6x - y = 2------1
y = 3x + 4---------2
Put eqn 2 in eqn 1
6x - (3x +4) = 2
6x - 3x - 4 = 2
3x = 6
x = 2
y = 3*2 + 4 = 6 + 4
= 10
Answer:
b I do believe
Step-by-step explanation:
can you help me
9514 1404 393
Answer:
m = (5x -6)/(43y -4)
Step-by-step explanation:
Subtract 4m+6 to separate m-terms from other terms.
5x +4m -(4m +6) = 43my +6 -(4m +6)
5x -6 = 43my -4m
5x -6 = m(43y -4) . . . . factor out m
(5x -6)/(43y -4) = m . . . . divide by the coefficient of m
The correct answer is 720 I did this problem long time ago hope this helps :)
I believe the answer to be only sequence A.
-Hope this helps, have a nice day! :)